ANALISIS KESIAPAN PENERAPAN POLA PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (PPK-BLUD) DI UPTD BALAI KESEHATAN INDERA MASYARAKAT (BKIM) PROVINSI SUMATERA BARAT TAHUN 2016 - Tuty Ernawati (Faculty of Public Health, Andalas University, 2018)
Regional Public Service Regency (RPSR) to provide services to the community without priority to seek profits, with existing data in unit Region Indra Center of West Sumatra Province has not been optimal yet in financial management, lack of the services have not standards, this study aims to evaluate the readiness of the implementation of the Financial Management Regional Public Service Regency (RPSR) at unit region Indra Centre of West Sumatera Province in 2016. This study uses qualitative study conducted in May to October 2016, with informants as much as 6 (six), data collection using indepth interview, document review and observation, analyzed by triangulation method and source. The results of the research show that the inputs are not well available yet, namely the regulations related to the implementation of the Financial Management Model of the Regional Public Service Regency (RPSR), human resources, limited budget, facilities and infrastructures are not yet eligible. In the process of substantive requirements have been eligible, technical requirements of service performance is quite good. and administrative requirements by assessing 6 documents have > 60% that is with a value of 80.3% which means the documents qualify administrative requirements. The conclusion of the study on the implementation of the Financial Management Model of the Regional Public Service Rgency (RPSR) at Unit Region Indra Centre West Sumatra, Unit Region Indra Centre is able to implement the full RPSR. Researchers suggest that it is necessary to draft the West Sumatra governor’s regulation on RPSR and complete administrative documents and improve the quality of services through improved management.